PERBEDAAN EFEKTIFITAS ANTARA LATIHAN FISIK DAN PROGRESSIVE MUSCLE RELAXATION (PMR) TERHADAP PENURUNAN KADAR GULA DARAH PUASA PADA PENDERITA DIABETES MELITUS TIPE 2 - Casman, Casman; Fauziyah, Yulia; Fitriyana, Ikha; Triwibowo, Cecep (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2015)
Diabetes Mellitus (DM) type 2 is one of metabolism problems caused by resistance or deficiency of insulin with common symptoms of hiperglycemia where the value of Fasting Blood Sugar (FBS) concentrate higher than 125 mg/dL. Physical exercise and PMR is recommended effort for DM  patient to reduce FBS concentrate. This research is conducted to know difference of effectiveness between physical exercise with PMR to reduction of FBS concentrate of DM type 2 patient in area of work Suraneggala Primary Health Center Cirebon Regency. This research used pra experiment with approach was one group pretest posttest design. Samples in research is 30 respondents selected used purposive sampling (15 respondents were given treatment of physical exercise, DM gymnastics 3 times per week for four month and 15 respondents were given treatment of PMR 2 times per day in the morning and afternoon for six days respectively). One session of exercise lasted 30 minutes. The  result of this research showed effectiveness between physical exercise effective with PMR to reduction of FBS concentrate is not difference, which suggest independent t test the value of p=0,927 (p>0,05). Physical exercise and PMR has same influence to reduce of FBS concentrate, the value of p=0,000. Means of FBS concentrate after physical exercise decreased from 171,93 to 121,73 mg/dL, means of FBS concentrate after PMR also decreased from 204,04 to 155,47 mg/dL. The conclusion of this research showed effectiveness between physical exercise with PMR to reduction of FBS concentrate in Diabetes Mellitus Type 2 patient is not difference.